Unraveling the Role of Loneliness in Depression: The Relationship Between Daily Life Experience and Behavior. Issue 2 (3rd April 2017) - van Winkel, Mark; Wichers, Marieke; Collip, Dina; Jacobs, Nele; Derom, Catherine; Thiery, Evert; Myin-Germeys, Inez; Peeters, Frenk
Abstract : Objective : Focusing on temporal associations between momentary (or state) loneliness, appraisal of social company, and being alone in daily life may help elucidate mechanisms that contribute to the development of prolonged (or trait) loneliness and major depressive disorder (MDD). We aim to examine if (a) a self-reinforcing loop between loneliness, negative appraisals of social company, and being alone in daily life may contribute to trait loneliness; (b) this possible self-reinforcing loop may also contribute to the development of MDD, by testing differences in temporal relationships between these social elements in participants who did or did not develop MDD during follow-up; and (c) any of these social elements at baseline predicted a MDD at follow-up. Methods : A female general population sample ( n  = 417) participated in an experience sampling method (ESM) study. Time-lagged analyses between loneliness, appraisal of social company, and being alone were examined at baseline, and their associations with the development of MDD during 20 months follow-up were investigated. Results : State loneliness was followed by an increase in negative appraisals of social company and a higher frequency of being alone. Further, negative appraisals of social company were associated with a higher frequency of being alone afterward. Only the latter was significant in the transition to MDD group. Trait loneliness predicted MDD during follow-up. Conclusions : Avoiding social contact after appraising company more negatively may contribute to the development of MDD.